Chapter 1 Introduction Urban ethics - conflicts over the good and proper life in cities - Ege, Moritz (Taylor & Francis, 2020)
This book delves into the ethical dimension of urban life: how should one live in the city? What constitutes a 'good' life under urban condition? Whose gets to live a 'good' life, and whose ideas of morality, propriety and 'good' prevail? What is the connection between the 'good' and the 'just' in urban life? Rather than philosophizing the 'good' and proper life in cities, the book considers what happens when urban conflicts and urban futures are carried out as conflicts over the good and proper life in cities. It offers an understanding of how ethical discourses, ideals and values are harmonized with material interests of different groups, taking up cases studies about environmental protection, co-housing schemes, political protest, heritage preservation, participatory planning, collaborative art production, and other topics from different eras and parts of the globe. This book offers multidisciplinary insights, ethnographic research and conceptual tools and resources to explore and better understand such conflicts. It questions the ways in which urban ethics draw on tacit moral economies of urban life and the ways in which such moral economies become explicit, political and programmatic.